Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil - de Oliveira, Verônica Maria; Jacobsen, Danny Eibye; Lana, Paulo (Zootaxa, 2018)
Four new species of Paranaitis are described from estuarine and continental shelf bottoms from southern and southeastern Brazil: Paranaitis chitinosa sp. nov., P. cirriformata sp. nov., P. assimetrica sp. nov., and P. cordiformata sp. nov. Paranaitis chitinosa sp. nov. is diagnosed by a proboscis with rows of conical and chitinous papillae alternating with dorsal chitinous bars, and the distal extremity covered with micropapillae, and dorsal cirri rounded and asymmetrical. Paranaitis cirriformata sp. nov. is similar to P. speciosa (Webster, 1879), previously recorded from Brazil, but differs by the presence of long and slender anal cirri. Paranaitis assimetrica sp. nov. differs from P. cordiformata sp. nov. by the presence of supra-acicular lobes that are considerably longer than the subacicular ones, and oval dorsal cirri. Paranaitis cordiformata sp. nov. has cordiform dorsal cirri and symmetrical supra- and sub-acicular lobes.